In Vitro Studies of Fe3O4‐ZIF‐8 Core–Shell Nanoparticles Designed as Potential Theragnostics. (23rd September 2020) - Ettlinger, Romy; Moreno, Natalia; Ziółkowska, Natalia; Ullrich, Aladin; Krug von Nidda, Hans‐Albrecht; Jirák, Daniel; Kerl, Kornelius; Bunzen, Hana
Abstract: Theragnostics represent a combination of therapy and diagnosis within one system. Herein, Fe3 O4 ‐ZIF‐8 core–shell nanoparticles are developed and suggested as candidates for theragnostic applications in cancer treatment. A drug loaded metal–organic framework ZIF‐8 (zeolitic imidazolate framework‐8) represents the therapeutic tool, while the Fe3 O4 core is included to enable the material visualization by magnetic resonance imaging (MRI). A reliable synthesis of Fe3 O4 ‐ZIF‐8 core–shell nanoparticles of an average size below 100 nm is reported. The nanoparticles are characterized by FT‐IR, TGA, XRPD, TEM, STEM‐EDS, DLS, ICP‐OES, CHN‐elemental analysis, SQUID measurements, and MRI. Moreover, their chemical stability and in vitro cytotoxicity against fibroblast and selected cancer cell lines are evaluated. As a model drug, arsenic trioxide—a promising anticancer drug—is used. The drug release can be triggered by a pH change from 7.4 to 6.0 and the nanoparticles can be visualized by MRI in vitro, thus a potential theragnostic agent for cancer treatment is developed. Abstract : Fe3 O4 ‐ZIF‐8 core–shell nanoparticles are a potential theragnostic agent suitable for the detection via magnetic resonance imaging and controlled pH‐responsive drug delivery, such as arsenic trioxide which is an uncommon but highly promising drug for cancer therapy. The integration of diagnostic information with pharmaceuticals is very attractive with regard to developing personalized medicine and advanced therapies.